Recent advances in single-cell subcellular sampling. Issue 36 (11th April 2023) - Sahota, Annie; Monteza Cabrejos, Anthony; Kwan, Zoe; Paulose Nadappuram, Binoy; Ivanov, Aleksandar P.; Edel, Joshua B.
Abstract : Recent advances and applications in subcellular sampling in single-cell systems are reviewed, along with their promise and current limitations. Abstract : Recent innovations in single-cell technologies have opened up exciting possibilities for profiling the omics of individual cells. Minimally invasive analysis tools that probe and remove the contents of living cells enable cells to remain in their standard microenvironment with little impact on their viability. This negates the requirement of lysing cells to access their contents, an advancement from previous single-cell manipulation methods. These novel methods have the potential to be used for dynamic studies on single cells, with many already providing high intracellular spatial resolution. In this article, we highlight key technological advances that aim to remove the contents of living cells for downstream analysis. Recent applications of these techniques are reviewed, along with their current limitations. We also propose recommendations for expanding the scope of these technologies to achieve comprehensive single-cell tracking in the future, anticipating the discovery of subcellular mechanisms and novel therapeutic targets and treatments, ultimately transforming the fields of spatial transcriptomics and personalised medicine.